DESIGN CHEMIMAGZ LEARNING MEDIA BASED ON CONTEXTUAL TEACHING AND LEARNING AS AN ALTERNATIVE LEARNING SOURCE ON ELEMENTAL CHEMISTRY MATERIAL - Kurniawati, Yenni; Putri, Rihani Himtari; Rosya, Aljeneri; Rahmah, Ati (MO.RI Publishing, 2024)
This research was instigated by chemistry learning media at Islamic Senior High School of Anshor Al-Sunnah Air Tiris that were not various especially on Chemical Element lesson. This research aimed at developing valid and practical Contextual Teaching and Learning based on Chemimagz learning media. It was a Research and Development (R&D) with a 4-D (Define, Design, Development, and Disseminate) model. This research was administered at the Islamic Senior High School of Anshor Al-Sunnah Air Tiris. The subjects of this research were 2 validators (the experts in media and material), a chemistry subject teacher, and 10 students at the Islamic Senior High School of Anshor Al-Sunnah Air Tiris. Interview, validation, and practicality test questionnaires were the techniques of collecting the data. The data obtained were analyzed by using qualitative and quantitative descriptive tests. The research findings showed that the validity level was 90% by the expert of media (very valid) and 88.42% by the expert of material (very valid), the practicality level was 89.33% by a chemistry subject teacher (very practical), and 90.1% by 10 students (very practical). Based on the research findings, it could be concluded that the availability of Contextual Teaching and Learning based Chemimagz learning media on Chemical Element lesson was valid and practical to be a learning media, and it could be used as an alternative learning resource.